General practice patients starting treatment for substance use problems: observations from two data sources across levels of care - Nicole Boffin; Jerome Antoine; Luk Van Baelen; Sarah Moreels; Kris Doggen (BMC, 2020)
Abstract Background In Belgium, the incidence of treatment episodes for substance use problems is monitored by the Network of Sentinel General Practices (SGP), and at higher, specialist care levels by the Treatment Demand Indicator (TDI) surveillance. Using both data sources, we examine 1) how patients starting specialist treatment for substance use problems on referral by their GP compare to those that were referred by non-GP caregivers; 2) how patients starting GP treatment for substance use problems without receiving concurrent specialist treatment compare to those who did. Methods Both surveillances are based on the TDI protocol for reporting data to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) on individuals starting treatment as a result of their substance use. Data from 2016 and 2017 were examined using 95% confidence intervals and multivariate logistic regression. Results According to TDI-data (n = 16,543), determinants of being referred by a GP (versus by a non-GP caregiver) for specialist treatment were age ≥ median (OR 1.25; 95% CI 1.13-1.38), education ≥ secondary level (OR 1.27; 95% CI 1.15-1.41), recent employment (OR 1.71; 1.56-1.88), recent stable accommodation (3.62; 95% CI 3.08-4.26), first treatment episode (OR 1.72; 95% CI 1.57-1.87), recent daily primary substance use (OR 1.46; 95% CI 1.33-1.59) and mono substance use (OR 1.23; 95% CI 1.04-1.48). Type of substance use was a significant determinant with higher odds of using pharmaceuticals (and alcohol) (OR 1.24; 95% CI 1.04-1.48), and lower odds of using cannabis only/primarily (OR 0.73; 95% CI 0.62-0.86), with reference to street drugs minus cannabis only/primarily. According to SGP data (n = 314), determinants of starting GP treatment without concurrent specialist treatment were recent employment (OR 2.58; 95% CI 1.36-4.91), first treatment episode (OR 2.78; 95% CI 1.39-5.55) and living in the Brussels or Walloon region (OR 1.97; 95% CI 1.06-3.66). Conclusions This study provides a useful insight into the general practice population treated for substance use problems. It shows that both surveillances consistently found a relatively favourable profile of general practice patients with substance use problems.